Argumentation Ab Homine in Philosophy - Leal, Fernando (Informal Logic)

(untitled) (Informal Logic, 2021)
Argumentation that uses the beliefs of one’s opponents to refute them is well known (ad hominem in the classical sense). This paper proposes that there is a hitherto unnoticed counterpart to it, to be called ab homine, in which speakers/writers argue through the manner in which they deliver a message. Since the manner of delivery can never be turned into a premise or premises, this form of argumentation—although somewhat resembling Aristotle’s ethos—is much closer to the peculiar force of Socratic elenchos.